A mentora literária de Guy de Maupassant - Hervot, Brigitte Monique [UNESP] (My University, 2010)
Laure Le Poittevin, Guy de Maupassant’s mother (1850-1893), had from his early childhood, a key role in the literary education of her son. This intelligent and sensitive woman, who was always passionate about arts, especially literature, to whom Maupasssant entrusted his projects and literary adventures, was his fi rst and eternal critic. In the letters he writes her, most of the time he takes the opportunity to plan and discuss his future projects; he presents a text in progress, he draws its guiding lines, he foreshadows its structures and points out some procedures based on a series of principles and recommendations of personal and universal values. Therefore, by reading again these letters, the readers nowadays can follow the writer’s daily life, the progression of his ideas and his literary development, the editing process of his book and his moments of sorrow and joy, anger and affection.

Laure Le Poittevin, mãe de Guy de Maupassant (1850-1893), teve um papel essencial na formação literária de seu filho, desde a sua mais tenra infância. Essa mulher inteligente, sensível, apaixonada pelas artes, em especial pela literatura, foi a primeira e eterna crítica a quem Maupassant confiou seus projetos e aventuras literárias. Nas cartas que escreve a sua mãe tem a oportunidade de, não raras vezes, planejar e discutir suas futuras obras: apresenta o texto que vai nascer, indica suas linhas mestras, prefigura suas estruturas e designa seus procedimentos por uma série de princípios e de recomendações de valor pessoal e universal. Assim, reler essas cartas possibilita ao leitor de hoje acompanhar seu cotidiano, bem como a evolução de suas idéias e sua produção literária, o preparo de seus livros, suas tristezas, suas alegrias, raivas e afetos.
The literary mentor of guy de maupassant
Keywords: Correspondence; Guy de Maupassant; Laure Le Poittevin; Correspondência; Guy de Maupassant; Laure Le Poittevin